HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Protein persulfidation in plants: a central regulator of multiple signaling pathways - Di Yang; Dengjing Huang; Xinfang Chen; Ailing Li; Huan Chen; Weibiao Liao (Plant Cell Reports, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Influencing factors of farmers’ willingness to revitalize and utilize rural homesteads under policy perception and resource endowment: Evidence from mountainous and hilly areas in Shandong Province - Xinjin Huan; Bowen Shan; Zhipeng Zhang; Guanghui Jiang; Ailing Wang; Linyao Chen (Journal of Mountain Science, 2026)

Quantitative genetic architecture of growth traits across sequential rearing phases in tiger pufferfish (Takifugu rubripes) - Yangzhen Li; Clémence Fraslin; Ailing Wu; Haomin Lyu; Haien Zhang; Diego Robledo; Robert Mukiibi; Widong Li; Songlin Chen (Aquaculture, 2026)

Characterization of the pathogenicity of newly emerged NADC30-Like PRRSV strains causing severe brain infections via twice inter-lineage recombination - Yuan Yang; Cheng Luo; Yixue Yan; Haoyu Chen; Feimin Xie; Ziyi Wang; Wei Wei; Mingsheng Cen; Xinyue Chen; Wenlin Huang; Xin Lan; Yu Feng; et al. (Veterinary Microbiology, 2026)

Leveraging real-time personal monitoring of air pollution and physical activity levels, and location tracking for mobility- and inhaled dose-based assessments of exposure and health risk - Ailing Jin; Yoo Min Park; Xiang Chen; Lu Liang; Peng Gong (Environmental Monitoring and Assessment, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Reducing chalkiness and enhancing quality and yield in hybrid indica rice at the middle panicle position through optimal water and nitrogen management - Yuanyuan Sun; Xiaojuan Yuan; Yinghan Luo; Guanzhou Luo; Kun Chen; Ailing Wang; Mingming Hu; Zongkui Chen; Zhiyuan Yang; Jun Ma; Yongjian Sun (Food Chemistry, 2025)

Shared e-bikes demand in urban mobility: Temporal heterogeneity, driving factors, and strategic implications - Ailing Yin; Xiaohong Chen; He Haitao; Andrew Morris; Quan Yuan; Xu Ma; Zhiwei Yang (Travel Behaviour and Society, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Volatile organic compounds from Bacillus velezensis FZB42 remodel Arabidopsis root architecture by an auxin-dependent mechanism - Ailing Ye; Liang Yue; Andéole Niyongabo Turatsinze; Xiaofan Xie; Zongyu Zhang; Gaofeng Chen; Lingling Wu; Qin Zhou; Yun Wang; Meilan Zhang; Yubao Zhang; Jiecai Zhao; et al. (Plant Cell Reports, 2025)

Fusarium cross-infection in medicinal herbs alters rhizosphere microbiomes and disrupts mycorrhizal functions under soil physicochemical imbalances - Andéole Niyongabo Turatsinze; Xiaofan Xie; Ailing Ye; Gaofeng Chen; Yun Wang; Liang Yue; Qin Zhou; Lingling Wu; Meilan Zhang; Zongyu Zhang; Jiecai Zhao; Yuexia Sha; et al. (Plant and Soil, 2025)

Identification of cell-surface receptors associated with 6-PPD quinone-induced reproductive toxicity in Caenorhabditis elegans after long-term and low-dose exposure: A primordial response including sword effect and shield effect - Shuhan Lei; Huanliang Liu; Bing Zhang; Ailing Chen; Xiaona Li; Yu Wu; Zhenyu Wang (Journal of Hazardous Materials, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

SlDCD and SlLCD increased the salt tolerance in tomato seedlings by enhancing antioxidant and photosynthesis capacity - Xinfang Chen; Dengjing Huang; Xiaoling Man; Ailing Li; Hua Fang; Siting Lu; Di Yang; Weibiao Liao (Plant Cell Reports, 2025)

Numerical Study on the Influence of Rudder Fillets on Submarine Wake Field and Noise Characteristics - Hao Yuan; Eryun Chen; Xingsheng Liu; Ailing Yang (Journal of Marine Science and Engineering, 2025)
The submarine rudder configuration and arrangement significantly impact its hydrodynamic performance. This paper takes the SUBOFF standard submarine model as the research object, constructs a geometrically parameterized rudder fillet structure based on parabolic parametric equations, and adopts the improved delayed separation vortex (IDDES) turbulence model to carry out numerical simulation research on the submarine rounding flow field with crossed and “X” rudder configurations. By comparing and analyzing the effects of different fillet parameters and rudder layouts on the generation mechanism of the horseshoe vortex, vortex system strength characteristics, and the distribution of the wake companion flow field at the velocity of 7.161 m/s, it is found that the introduction of the rudder fillet structure can effectively destabilize the horseshoe vortex and significantly reduce the axial velocity inhomogeneity of propeller plane. In addition, the improvement effect of the flow field in the near-axis region (r/R ∈ (0, 0.5)) is particularly significant. Compared with the crossed rudder, the “X” layout shows better flow control performance, with the maximum reduction in the axial relative velocity of the propeller plane surface reaching 49.34%, which is 24.25% higher than that of the SUBOFF baseline model, and the addition of two distributions of rudder fillets can reduce the hydrodynamic noise of the submarine by 4.6 dB vs. 5.6 dB at most. The results provide an essential hydrodynamic basis for optimizing the submarine rudder system.

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Association between short-term ambient particulate matters and acute liver injury outpatient visits: A hospital-based study - Chen Xu; Zelin Tian; Hongyu Zhong; Yumeng Zhou; Ning Du; Wenjie Zhang; Chunyan Yao; Ailing Ji; Xuan Zhang; Tongjian Cai (Atmospheric Environment, 2024)

The role of BTG2/PI3K/AKT pathway-mediated microglial activation in T-2 toxin-induced neurotoxicity - Xiukuan Li; Jinyun Long; Chunyan Yao; Xiaoling Liu; Na Li; Yumeng Zhou; Dawei Li; Guiyuan Xiong; Kexue Wang; Yuhui Hao; Ka Chen; Ziyuan Zhou; et al. (Toxicology Letters, 2024)

A pH-responsive MOFs@MPN nanocarrier with enhancing antifungal activity for sustainable controlling myclobutanil release - Yushan Hou; Yaowei Zhang; Yanyan Huang; Ailing Zhou; Jiatong Han; Kexin Yang; Yiming Zhao; Jie Zhou; Jing Wang; Ge Chen; Xiaomin Xu; Donghui Xu; et al. (Chemical Engineering Journal, 2024)

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

How electric bikes reduce car use: A dual-mode ownership perspective - Ailing Yin; Xiaohong Chen; Frauke Behrendt; Andrew Morris; Xiang Liu (Transportation Research Part D: Transport and Environment, 2024)

Does climate policy uncertainty drive the extreme spillovers of carbon-energy-shipping markets? - Yanhui Chen; Ailing Feng; Jackson Jinhong Mi (Journal of Environmental Management, 2024)

Sub-nano porous graphene-based membranes enabled by in-situ-grown ZIF-8 for enhanced CO2 capture - Lei Zhang; Yong Zhao; Hao Yu; Liang Chen; Xiang Liu; Ailing Zhang; Zhibin Deng; Jian Zhen Ou (Chemical Engineering Journal, 2024)

Increased risk of preterm birth due to heat exposure during pregnancy: Exploring the mechanism of fetal physiology - Liyun Wang; Chunying Zhang; Jiangli Di; Qiong Wang; Meng Ren; Aiqun Huang; Sidi Chen; Wei Zhao; Huanqing Hu; Ailing Wang; Qian Di; John S. Ji; et al. (Science of The Total Environment, 2024)

Triassic oceanic–continental transition of the Ganzi–Litang Ocean basin: Evidence from high-Mg andesites and Nb-enriched basalts in the Litang area, Eastern Tibet - Songtao Yan; Ailing Ding; Xuejian Dai; Tao Liu; Hu Li; Hongrui Dai; Peng Chen; Qingsong Wu; Lidong Zhu (Journal of Asian Earth Sciences, 2024)

Experimental and kinetic study on pyrolysis and combustion characteristics of pesticide waste liquid - Long Yang; Zewu Zhang; Ailing Chen; Wenchao Mao; Zhengyang Zhu; Yue Zhao; Liqi Zhang (Journal of Environmental Chemical Engineering, 2024)

Adaptive responses of Dermacoccus abyssi HZAU 226 to lysozyme stress - Xinshuai Zhang; Yuanyuan Chen; Ailing Guo; Jun Lv (Food Bioscience, 2024)

Granular bacterial inoculant alters the rhizosphere microbiome and soil aggregate fractionation to affect phosphorus fractions and maize growth - Xiaofan Xie; Yang Liu; Gaofeng Chen; Andéole Niyongabo Turatsinze; Liang Yue; Ailing Ye; Qin Zhou; Yun Wang; Meilan Zhang; Yubao Zhang; Zhongping Li; Lam-Son Phan Tran; et al. (Science of The Total Environment, 2024)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Discovery of acylated isoquercitrin derivatives as potent anti-neuroinflammatory agents in vitro and in vivo - Jie Liu; Ailing Hui; Jinghe Wang; Qingfeng Hu; Shengnan Li; Yuanli Chen; Zeyu Wu; Wencheng Zhang (Chemico-Biological Interactions, 2023)

The inhibitory mechanism of 2-amino-3,8-dimethylimidazo [4,5-f] quinoxaline (MeIQx) formation by ultraviolet-gallic acid (UV-GA) during the oil-frying process of squid - Huawei Ma; Weijie Chen; Min Lv; Xiaobao Qi; Qiufeng Ruan; Chuanyan Pan; Ailing Guo (Food Chemistry, 2023)

Increased ozone exposure is associated with decreased risk of epilepsy: A hospital-based study in southwest China - Yumeng Zhou; Laixin Zhou; Lili Yang; Jianghong Liu; Nan Wang; Enjie Tang; Xiaoling Liu; Chunyan Yao; Hua Xiao; Xiangjun Chen; Qian Zhang; Feng Liu; et al. (Atmospheric Environment, 2023)

Mphy gene reveals the involvement of light source in the regulation of pigment metabolism in Monascus ruber - Weidong Li; Ailing Li; Wanjun Yu; Mianhua Chen; Guozhong Zhao; Yurong Wang (Food Bioscience, 2023)

The role of extreme high humidex in depression in chongqing, China: A time series-analysis - Yumeng Zhou; Ailing Ji; Enjie Tang; Jianghong Liu; Chunyan Yao; Xiaoling Liu; Chen Xu; Hua Xiao; Yuegu Hu; Yuexu Jiang; Dawei Li; Ning Du; et al. (Environmental Research, 2023)

Molecular mechanisms of cell death in bronchopulmonary dysplasia - Xianhui Deng; Zhidan Bao; Xianpeng Yang; Yingzi Mei; Qin Zhou; Ailing Chen; Renqiang Yu; Yongjun Zhang (Apoptosis, 2023)

Lipopolysaccharide induces inflammatory microglial activation through CD147-mediated matrix metalloproteinase expression - Chunyan Yao; Xiaoling Liu; Yan Tang; Chunmei Wang; Chenggang Duan; Xiaoyan Liu; Mingliang Chen; Yumeng Zhou; Enjie Tang; Ying Xiang; Yafei Li; Ailing Ji; et al. (Environmental Science and Pollution Research, 2022)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Characterization and genome analysis of novel Klebsiella phage Henu1 with lytic activity against clinical strains of Klebsiella pneumoniae - Tieshan Teng; Qiming Li; Zhengguo Liu; Xianghui Li; Zizheng Liu; Hanshu Liu; Fangyan Liu; Longxiang Xie; Huijuan Wang; Lei Zhang; Dongdong Wu; Mingliang Chen; et al. (Archives of Virology, 2019)

Development of β-elemene and Cisplatin Co-Loaded Liposomes for Effective Lung Cancer Therapy and Evaluation in Patient-Derived Tumor Xenografts - Mingxiang Cao; Mengmeng Long; Qiuping Chen; Yapeng Lu; Qianqian Luo; Yue Zhao; Ailing Lu; Cunwang Ge; Li Zhu; Zhongping Chen (Pharmaceutical Research, 2019)

Nuciferine alleviates LPS-induced mastitis in mice via suppressing the TLR4-NF-κB signaling pathway - Xingxing Chen; Xintian Zheng; Min Zhang; Huifang Yin; Kangfeng Jiang; Haichong Wu; Ailing Dai; Shoushen Yang (Inflammation Research, 2018)

Enhancement of brain-targeting delivery of danshensu in rat through conjugation with pyrazine moiety to form danshensu-pyrazine ester - Ailing Hui; Huayang Yin; Zheng Zhang; An Zhou; Jingchao Chen; Li Yang; Zeyu Wu; Wencheng Zhang (Drug Delivery and Translational Research, 2018)

Celastrol specifically inhibits the activation of NLRP3 inflammasome - Xuesong Sang; Yihui Chen; Wei Chen; Jing Xie; Guangxun Meng; Jin Zhong; Taisheng Li; Ailing Lu (Science China Life Sciences, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Co-production of lipids, eicosapentaenoic acid, fucoxanthin, and chrysolaminarin by Phaeodactylum tricornutum cultured in a flat-plate photobioreactor under varying nitrogen conditions - Baoyan Gao; Ailing Chen; Wenyuan Zhang; Aifen Li; Chengwu Zhang (Journal of Ocean University of China, 2017)

A pH-Sensitive Nanocarrier for Tumor Targeting - Ligang Chen; Chen Fu; Yajun Deng; Wei Wu; Ailing Fu (Pharmaceutical Research, 2016)

Microarray data uncover the genome-wide gene expression patterns in response to heat stress in rice post-meiosis panicle - Xianwen Zhang; Hairong Xiong; Ailing Liu; Xiaoyun Zhou; Yan Peng; Zhuoxue Li; Guangyu Luo; Xiangrong Tian; Xinbo Chen (Journal of Plant Biology, 2014)

Overexpression of Transcription Factor OsWR2 Regulates Wax and Cutin Biosynthesis in Rice and Enhances its Tolerance to Water Deficit - Xiaoyun Zhou; Matthew A. Jenks; Juan Liu; Ailing Liu; Xiangwen Zhang; Jianhua Xiang; Jie Zou; Yan Peng; Xinbo Chen (Plant Molecular Biology Reporter, 2014)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)

Hydrological Simulation by SWAT Model with Fixed and Varied Parameterization Approaches Under Land Use Change - Jinkang Du; Hanyi Rui; Tianhui Zuo; Qian Li; Dapeng Zheng; Ailing Chen; Youpeng Xu; C.-Y. Xu (Water Resources Management, 2013)

The novel 5bp deletion polymorphism in the promoter region of bovine ACRP30 gene - Liangzhi Zhang; Hong Chen; Xianyong Lan; Cunfang Zhang; Li Zhang; Ailing Zhang; Qin Zhang; Cunlei Lei; Hanyang Zhang (Molecular Biology Reports, 2009)